Textualising travel in André Gide and Henri Michaux - Geary Keohane, Elizabeth. (Trinity College (Dublin, Ireland). Department of French, 2013)
This thesis considers the interplay between real and imaginary travel in the works of Andre Gidé and Henri Michaux, whilst also positing that this interplay can manifest itself in an intermediate form, anticipated travel. The methodology of my project involves focusing on the textualisation of travel. That is to say, my project favours a focus on the way(s) the author represents journeys, one, therefore, which does not seek to classify texts solely on the basis of whether the journey they describe has actually taken place or not. Indeed, the texts relating the real or actual voyages of Gide and Michaux will be seen to inform and be informed by each author’s extensive experimentation with the imaginary voyage. The generic permutations and variations that encompass the travel narratives ultimately produced (journal, récit, sotie, traité, roman, [prose] poetry, and any combination thereof) will also be taken into account. In remaining attuned to their experimentation with genre, my approach allows me to explore the intertextual connections linking representations of real and imaginary travel in Gidé and Michaux Both works of fiction and texts based on journeys undertaken by the writer in question therefore form my corpus of study, though it is understood that the representation of a real journey can feed into fiction as much as fiction seeps into purportedly faithful accounts of travel. Chapter 1 considers three of Gidé’s works written in the 1890s as key texts in his development as a writer who travels, texts that experiment with ways to relate and interrogate the experience of travel. The rich links that exist amongst the journeys central to Le Voyage d ’Urien, Paludes and El HadJ are uncovered. This thesis posits the idea that Gidé is using the creative freedom inherent to the enterprise of fiction in order to approach travel as a subject, theme and narrative motor in these formative years of his career; in short, he is experimenting with the textualisation of travel. Les Nourritures terrestres is seen as a work which synthesises many of the principal findings and persistent concerns of the other three travel texts of the same period studied here - yet, at the same time, it introduces representations of real travel, therefore looking forward to and informing Gidé’s later narratives relating journeys of physical displacement. Chapter 2 considers the interplay between Michaux’s narratives Ecuador and Un Barbare en Asie, both of which are based on real journeys, as well as exploring to what extent his later narratives on imaginary countries are rooted in these texts. It also investigates the way Michaux’s dual status as artist-writer informs his verbal expression of the travel experience. Chapter 3 analyses Gidé’s year-long trip around West Africa and the narratives it produced - and continued to generate upon his return (in the form of reactions and clarifications), as well as their exploration of identity formation in terms of travel. Chapter 4 explores Gide’s account of his trip to the USSR, tracing the way in which a country under construction can destabilise the construction of a travel narrative that attempts to negotiate a destination in flux. Chapter 5 returns to Michaux, and analyses the ways in which his Ailleurs collection, a series of narratives based on imaginary voyages, revisits and often revises problematic aspects of his earlier experiences in textualising real journeys. This shows the extent to which textualising travel can also operate as a corrective exercise. It will therefore be seen in this thesis that, rather than compartmentalising an author’s work into expressions of real and imaginary travel so that they might be considered separately, a more fruitful analysis of an author’s engagement with travel can emerge from studying the way(s) in which the author approaches the textualisation of travel. Such an analysis uncovers the interplay and overlap between real and imaginary travel that can often generate - as much as permeate - a text.
Embargo End Date: 2022-01-01
Keywords: Languages, Literatures & Cultural Studies, Ph.D.; Ph.D. Trinity College Dublin, 2013